Rice in the Nigerian economy and agricultural policies - Gyimah-Brempong, Kwabena; Johnson, Michael E.; Takeshima, Hiroyuki (University of Pennsylvania Press, 2016)
Over the past few decades, rice has become one of the leading food staples in Nigeria, surpassing cassava in food expenditure. Throughout this period, consumption has increased faster than production, resulting in a growing dependency on imports. By 2014, about half of the rice consumed in Nigeria was imported. As the most populous country in Africa south of the Sahara (SSA), Nigeria has quickly become the leading importer of rice on the continent and, more recently, in the world.